A computed tomography and endoscopy assisted study of the anatomical variations of lateral wall of nose in patients of chronic rhinosinusitis- our experience at a tertiary care centre - Suligavi, Shashidhar S.; Fathima, Afshan; Patil, Mallikarjun N.; Doddamani, S. S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic rhinosinusitis (CRS) is a common and persistent illness that ENT surgeons encounter in their day to day practice. The lateral wall of the nose contains the ostiomeatal unit which is the key area targeted in the management of CRS. The lateral wall of nose shows several variations which can alter the course of the disease. It is of utmost importance for the ENT surgeon to be aware of these variations as they decide the overall line of management. The objectives of the study was to study the anatomical variations of the lateral wall of nose using computed tomography (CT) scans and nasal endoscopy in patients of chronic rhinosinusitis. Methods: A one year study from April 2015 to March 2016 involving 50 patients attending the ENT outpatient department clinically diagnosed as CRS using the criteria of task force on rhinosinusitis were included in the present study. Patients underwent a CT scan and DNE and the anatomical variations of the lateral wall of nose were studied. Results: Concha bullosa was the most common anatomic variation noted in 20 (40%) of the total 50 patients. The other anatomic variations noted were uncinate process variations in 15(30%) patients, agger nasi cells in 3 (6%) patients, hypoplastic middle turbinate in 1 (2%) patient, paradoxical middle turbinate in 2(4%) patients, bulla ethmoidalis in 4 (8%) patients and Haller cells in 1 (2%) patient. Conclusions: The lateral wall of nose is made up of several structures showing variations which can lead to the development CRS and affect the overall management. They should be evaluated pre-operatively in order to avoid intraoperative complications. CT scan and DNE both complement each other and effectively evaluate the anatomical variations of the lateral wall of nose.